On the relationship between critical thinking skills, biology learning outcomes, and their visual learning style - Witri Noor Ayu Andini; Purwati Kuswarini Suprapto; Vita Meylani (Universitas Wiralodra, 2022)
Critical thinking ability refers to an individual's capacity for in-depth thought due to the development of diverse thinking talents, including cognitive capabilities, in response to the acquired information. The purpose of the present study was to investigate the relationship between critical thinking skills, biology learning outcomes, and the visual learning style of students. The study used the correlational research method to ascertain the association between critical thinking abilities and biology learning outcomes among students with a visual learning style in class XI MIPA SMAN 6 Tasikmalaya. To this end, 40 students with predominating visual learning styles were selected from 137 students from class XI MIPA 4-7 at SMAN 6 Tasikmalaya. They were asked to fill in a learning style questionnaire with 23 statements. Moreover, they were asked to answer the nine-question evaluation of students' critical thinking abilities regarding biology topics. Students completed learning outcomes from the Year-End Assessment (PAT) grade XI MIPA in biological issues. Pearson product-moment correlation was employed to answer the research question. The result of the study indicated there is critical thinking ability had a limited association with learning outcomes in students who chose a visual learning approach. The correlation coefficient (R) of 0.365 and coefficient of determination (R2) of 0.133 attested to this. The findings revealed that both critical thinking skills and visual learning styles could predict learning outcomes.